CHALLENGES AND OPPORTUNITIES FOR DIGITAL TRANSFORMATION IN COMPANY OPERATIONAL MANAGEMENT - Farida, Farida (INFOKUM, 2023)
Digital transformation has become a necessity in the modern business world to increase company efficiency and competitiveness. This research aims to investigate the challenges and opportunities faced by companies in adopting digital transformation, especially in the context of operational management. This research uses a qualitative approach with descriptive methods. The research results show that digital transformation in company management brings a number of challenges and opportunities that need to be considered. Key challenges include employee resistance to change, increasingly critical data security, significant implementation costs, and the complexity of integrating new technology with existing systems. However, on the other hand, great opportunities also open up with the ability to increase operational efficiency through process automation, personalization of customer service, and responsiveness to market changes with real-time data analysis. Digital transformation also provides flexibility and scalability, allowing companies to adapt operations to changing needs and better deal with business growth. Therefore, companies need to be wise in overcoming challenges, maximizing opportunities, and taking strategic steps to successfully adopt digital transformation in their operational management.